INTERNET ADDICTION IN MEDICAL STUDENTS - Haroon, Zeeshan; Zeb, Zainab; Javed, Zanib; Awan, Zainab; Aftab, Zarmeena; Talat, Warda (Journal of Ayub Medical College Abbottabad, 2019)
Background: Internet is a technology that was designed to facilitate research and official communication. According to Internet World Stats, there are 3.36 billion internet users in the world. The internet usage has increased by 832.5% in the world since 2005. In Pakistan there are 25 million active users using internet. It is a multi-dimensional behavioural disorder that manifest in various physical, psychological and social disorders and causes a number of functional and structural changes in brain with related various comorbidities. There is paucity of local researches on this topic but the access to internet and its use is enormous. This study was conducted to find the magnitude of internet addiction in medical students. Methods: It was a descriptive cross-sectional study carried out in Ayub Medical College, Abbottabad. One hundred & forty-eight students were selected in the survey using stratified random sampling. The data was collected using academic and school competence scale and internet addiction diagnostic criteria. Results: In this study, 11 (7.86%) fulfilled the criteria for internet addiction. Most of the students 93 (66.3%) used internet to visit social media applications. Majority of the students 10 (90.9%), showed tolerance as major non-essential symptom of internet addiction. Internet addicts showed significant p=0.01 below average academic performance when compared to non-addicts. Internet addiction showed a significant p=0.03 gender association with internet addiction more prevalent in females than males (12.5% Vs 2.9%). Conclusion: This study shows that excessive internet use leads to its addiction and is an entity of concern among medical students. Keywords: internet addiction; behavioural disorders; medical students; social media.